„Kolęda, Nowe Lato i Szczodry Dzień” — geneza, rozwój i schyłek gatunku w XVII wieku - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article is proving that works arisen from the tradition of wishing carol, in which titles appeared a formula „Carol, The New Year and the Generous Day”, constitute a separate literary genre. What is more, works, which belong to it could exist in two forms: unified and cyclical. The genesis of the genre is regarded to appear in combining into one group the motives and symbols of the Christian holidays (from the Christmas through the Circumcision / the New Year to the Epiphany). These types of lyrics were printed from the very beginning to the half of the 17th century. The article therefore is creating the profile of dozen texts saved to our times.